The impact of Industry 4.0 on bottleneck analysis in production and manufacturing: Current trends and future perspectives. (December 2022) - Mahmoodi, Ehsan; Fathi, Masood; Ghobakhloo, Morteza
Highlights: I4.0 design principles and technologies considered in BA are identified. The potential for novel technology-driven BA methods is discussed. The effect of I4.0 on the future bottleneck analysis is investigated. The impact of BA methods on manufacturing productivity improvement is discussed. Abstract: Bottleneck analysis, known as one of the essential lean manufacturing concepts, has been extensively researched in the literature. Recently, there has been a move towards using new Industry 4.0-based concepts and technologies in the development of bottleneck analysis. However, the interrelations between bottleneck analysis and Industry 4.0 have not been studied thoroughly. The present study addresses this gap and performs a systematic literature review on articles available in major scientific databases (i.e., Web of Science and Scopus) to investigate the impact of Industry 4.0 on the advancement of bottleneck analysis in production and manufacturing. Bibliometric analysis and content review were performed to extract the quantitative and qualitative data. Results revealed that only five out of 15 design principles and five out of eleven technologies of Industry 4.0 were addressed previously in developing bottleneck analysis methods. In addition to highlighting the existing gaps in the literature and proposing topics for future research, several potential development streams are proposed by studying the design principles and technologies of Industry 4.0, which have not been considered in bottleneck analysis before.